Overview of the Collective Benefits of Members of the Muhammadiyah Student Association (IMM) - Nisa Kurnia Sari; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the problem of collective efficacy in members of the Muhammadiyah Student Association (IMM), this study aims to describe the collective efficacy of members of the IMM Organization at Muhammadiyah University of Sidoarjo quantitatively descriptively. The population in this study were 474 members. The sample used is 198 members based on an error rate of 5% in the table developed by Isaac and Michael. The sampling technique used in this study is the proportional random sampling technique, the data collection technique in this study uses a psychological scale, namely the collective efficacy scale in the form of a Likert scale. The results of the reliability test are 0.917, the results also show that the collective efficacy of members in the IMM organization at Muhammadiyah University of Sidoarjo is mostly in the moderate category of 67.7%, with details of collective efficacy in the high category of 18.7% and the low category of 13. 6%. The conclusion is that members of the IMM organization at Muhammadiyah University of Sidoarjo are quite capable of instilling a sense of group trust in achieving organizational goals or targets.